The miracle of life [videorecording] - Erikson, Bo G.; Lofman, Carl O.; Mansfield, John.; Nixon, Bebe. ([S.l.] Swedish Television in association with WGBH Educational Foundation, 1983)
This Emmy-award winning program follows the evolution of the fetus using microscopic photography.
Title animation generated at the New York Institute of Technology.
VHS.
Credits : Editor, Carl O. Lofman ; Narrator, Anita Sangiolo ; Photographer, Lennart Nilsson.
Keywords: Human reproduction